2018
DOI: 10.1021/acs.energyfuels.7b02844
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Water Interactions with Petroleum-Derived and Synthetic Aviation Turbine Fuels

Abstract: While undesirable in aviation fuel systems, water is both ubiquitous and tenacious; thus, interactions between water and aviation turbine fuel occur regularly. From a fuel user perspective, it is important to know, understand, and be able to predict such fuel–water interactions, e.g., water solubility, water settling rate, and interfacial tension, for proper mitigation. We explore these interactions as well as surface tension of both petroleum-derived and alternative jet fuels to compare potential differences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 26 publications
(82 reference statements)
3
18
0
Order By: Relevance
“…Figure 4 From figure 4, the water solubility curve has been established as an exponential function by CRC; hence the decrease in solubility at high temperature in figure 4a deviates from the physical expectation. Water solubilities in alternative fuels in work reported by West et al all fit an exponential trend as reported by CRC in figure 4a), and no form of limit was noticed above 30 ºC as reported by Charro et al [42] [61]. Even though both authors the experimental technique adopted by the authors.…”
Section: Water Solubility/settling In Jet Fuelsupporting
confidence: 54%
See 3 more Smart Citations
“…Figure 4 From figure 4, the water solubility curve has been established as an exponential function by CRC; hence the decrease in solubility at high temperature in figure 4a deviates from the physical expectation. Water solubilities in alternative fuels in work reported by West et al all fit an exponential trend as reported by CRC in figure 4a), and no form of limit was noticed above 30 ºC as reported by Charro et al [42] [61]. Even though both authors the experimental technique adopted by the authors.…”
Section: Water Solubility/settling In Jet Fuelsupporting
confidence: 54%
“…However, water is always present and cannot be eliminated. Therefore, the water content should be kept to a minimal level [61]. Typically, a water-saturated fuel contains between 40 and 80 ppm dissolved water at ambient temperature (about 21 °C) [8].…”
Section: Water and Its Behaviour In Jet Fuelmentioning
confidence: 99%
See 2 more Smart Citations
“…Some other disadvantages of this fuel are lower oxidation stability, higher cloud point, and lower energy content in comparison with petroleum-based diesel [14]. The observational and modeling studies for the establishment of these properties become important because the concentration on usages of the biofuels and their properties have been grown [15,16]. For example, the density of biodiesel is the important property that has a significant matter in the thermophysical process.…”
Section: Introductionmentioning
confidence: 99%